The influence of rat mesenchymal stem cell CD44 surface markers on cell growth, fibronectin expression, and cardiomyogenic differentiation on silk fibroin – Hyaluronic acid cardiac patches - Yang, Ming-Chia; Chi, Nai-Hsin; Chou, Nai-Kuan; Huang, Yi-You; Chung, Tze-Wen; Chang, Yu-Lin; Liu, Hwa-Chang; Shieh, Ming-Jium; Wang, Shoei-Shen (Biomaterials, 2010)
Since MSCs contain an abundant of CD44 surface markers, it is of interesting to investigate whether CD44 on rat MSC (rMSCs) influenced cell growth, fibronectin expression and cardiomyogenic differentiation on new SF/HA cardiac patches. For this investigation, we examined the influences of rMSCs with or without a CD44-blockage treatment on the aforementioned issues after they were cultivated, and further induced by 5-aza on SF and SF/HA patches. The results showed that the relative growth rates of rMSCs cultured on cultural wells, SF/HA patches without or with a CD44-blockage treatment were 100%, 208.9 ± 7.1 (%) or 48.4 ± 6.0 (%) ( n = 3, for all), respectively, after five days of cultivations. Moreover, rMSCs cultivated on SF/HA patches highly promoted fibronectin expressions (e.g., 1.8 × 10 5/cell, in fluorescent intensity) while cells with a CD44-blockage treatment markedly diminished the expressions (e.g., 1.1 × 10 4/cell, in fluorescent intensity) on same patches. For investigating possible influences of CD44 surface markers of rMSCs on their cardiomyogenic differentiation, the expressions of specific cardiac genes of cells were examined by using real-time PCR analysis. The results indicated that 5-aza inducing rMSCs significantly promoted the expressions of Gata4, Nkx2.5, Tnnt2 and Actc1 genes (all, P < 0.01 or better, n = 3) on SF/HA patches compared with those expressions on SF patches and for cells with a CD44-blockage treatment on SF/HA patches. Furthermore, the intensity of the expressions of cardiotin and connexin 43 of 5-aza inducing rMSCs were markedly higher than those of cells with a CD44-blockage treatment after they were cultured on SF/HA patches. Through this study, we reported that CD44 surface markers of rMSCs highly influenced the proliferations, fibronectin expressions and cardiomyogenic differentiation of rMSCs cultivated on cardiac SF/HA patches.